Social Media, E‐Health, and Medical Ethics. - Terrasse, Mélanie; Gorin, Moti; Sisti, Dominic (Hastings Center Report, 2019)
Given the profound influence of social media and emerging evidence of its effects on human behavior and health, bioethicists have an important role to play in the development of professional standards of conduct for health professionals using social media and in the design of online systems themselves. In short, social media is a bioethics issue that has serious implications for medical practice, research, and public health. Here, we inventory several ethical issues across four areas at the intersection of social media and health: the impact of social networking sites on the doctor‐patient relationship, the development of e‐health platforms to deliver care, the use of online data and algorithms to inform health research, and the broader public health consequences of widespread social media use. In doing so, we review discussions of these topics and emphasize the need for bioethics to focus more deeply on the ways online technology platforms are designed and implemented. We argue that bioethicists should turn their attention to the ways in which consumer engagement, bias, and profit maximization shape online content and, consequently, human behavior and health. We also offer a set of recommendations and suggest future directions for addressing ethical challenges in these domains.